From public deficits to public defects: How journalists embraced technocratic explanations for the Post-Truth Era - Gordon Katic (Facts & Frictions)
Since 2016, we have been living in what many scholars call a ‘post-truth era,’ which is said to be dominated by mistrust, misinformation, anti-expert populism, and out-right science denial. Usually, this story focuses on technical issues in our information sphere, or on the public’s failings. Conversely, I am informed by critical approaches in science studies that stress how public mis/understanding of science is symptomatic of deeper social and political divides between experts and publics. In that spirit, this polemical article focuses its critical attention on science itself, and more specifically the journalists who disseminate their work. I conduct an exploratory critical discourse analysis on a small selection of the most popular and critically-acclaimed journalists of science, research, and expertise (including Michael Lewis, Ezra Klein, Ed Yong, and others). My analysis reveals an emerging model of science communication for the post-2016 era. Earlier, journalists embraced a public deficit model that assumed a deficient public could be paternalistically educated towards accepting scientific insights. Today, that view is being supplemented (and sometimes supplanted) by something I call the public defect model. In this model, journalists see publics as cognitively defective, and therefore resistant—if not outright impervious—to intelligent persuasion. My paper contributes new theoretical insights to the study of science journalism. Furthermore, I offer a polemical intervention against the creeping anti-democratic tendencies of some of the most well-respected journalists of our time, as well as suggestions for journalists and journalism educators who wish to combat these tendencies.